The leadership moment nine true stories of triumph and disaster and their lessons for us all - Useem, Michael (Tantor Media, 2020)
Are you ready for the leadership moment' Learn valuable lessons from the stories of:- Merck's Roy Vagelos, who commits millions of dollars to develop a drug needed only by people who can't afford it- Eugene Kranz, who struggles to bring the Apollo 13 astronauts home after an explosion rips through their spacecraft- Arlene Blum, who organizes the first women's ascent of one of the world's most dangerous mountains- Nancy Barry, who leads Women's World Banking in the fight against Third World poverty- Wagner Dodge, who faces the decision of a lifetime as a fast-moving forest fire overtakes his firefighting crew- And more.